Acute safety, cardiovascular, perceptual and neuromuscular responses to autoregulated and non-autoregulated blood flow restriction training during elbow rehabilitation in people with hemophilia - Ogrezeanu, Daniel C.; Tur-Boned, Andrea; Rolnick, Nicholas; Carrasco, Juan J.; Cruz-Montecinos, Carlos; Calatayud, Joaquín; Bonanad, Santiago; Pérez-Alenda, Sofía (Frontiers in Sports and Active Living, 2025)
IntroductionLow-load resistance training with concurrent blood flow restriction (BFR) provides strength and hypertrophy benefits to healthy individuals and some clinical populations. This is the first study assessing safety and physiological responses of autoregulated (AUTO) and non-autoregulated (NAUTO) BFR protocols in people with hemophilia (PWH). Therefore, this study aimed to evaluate the acute safety, cardiovascular, neuromuscular and perceptual responses during AUTO and NAUTO BFR training in PWH.MethodsEleven severe PWH under prophylaxis performed two sessions of elbow flexion and extension using elastic bands at 50% of the limb occlusion pressure (LOP) with different BFR settings (AUTO vs. NAUTO). Safety, cardiovascular parameters, rating of perceived exertion, elbow pain and pressure algometry were assessed at different timepoints. High-density surface electromyography activity and its spatial distribution were determined for biceps and triceps brachii.ResultsBoth BFR conditions were safe in PWH. AUTO provided a hypotensive and hypoalgesic acute response, albeit without between-group differences. Triceps brachii showed differences in spatial distribution, and greater activity with AUTO in the last 3 cycles of the first 3 sets. Although no major differences were found between both conditions in perceptual responses, AUTO condition increased VAS scores during both exercises. No adverse events were observed.ConclusionsBFR at 50%LOP during arm exercise with either AUTO or NAUTO appears to be equally safe in PWH, but AUTO showed trends for improved cardiovascular and neuromuscular responses. AUTO produced a hypotensive and hypoalgesic acute post-exercise response, albeit without between-group differences, a greater activation in triceps brachii, and higher values of pain. No serious adverse events were observed.